Szerkesztői előszó - Csorba, Dávid; Fazakas, Gergely Tamás; Imre, Mihály; Tóth, Zsombor (Studia Litteraria, 2012)
Although the construction of martyrdom has come to the forefront in recent international research on Protestantism, there are only a few Hungarian scholars who have already examined the early modern representations of different religious and national identities from this aspect. The articles collected in this volume aim at shifting the centre of Western research on early modern martyrdom towards the Carpathian Basin. We analyse the interconnections, patterns and differences of textual and visual representations of Protestant martyrdom, and explore how the various Western martyr traditions were interpreted and acculturated in early modern Hungary. This volume is based on a conference held in 2011 at the University of Debrecen, and organised by the Research Group for Reformation and Early Modern Cultural History, in cooperation with other scholars of several Hungarian universities. We participate in a collaborative research project, supported by OTKA and TÁMOP funds, in order to extend our understanding of early modern martyrdom.